Egypt in the Eighteenth Dynasty: Influences Leading to the Reforms of Akhenaten - Harschlip, Lincoln C. A. (My University, 2011)
This paper focuses on the Eighteenth Dynasty of Egypt and the early reign of Amenophis IV, or Akhenaten. Akhenaten is known mostly for his radical reforms which focused on changing the Egyptian state religion from its original pantheon of gods to a new, pseudo-monotheistic cult centered on the Aten, or Sun disk. This paper will explore the influences, both domestic and foreign, which brought about these drastic changes.
Keywords: Egypt--History--Eighteenth dynasty, ca. 1570-1320 B.C.; Egypt--Religion--History; Akhenaton, King of Egypt